DESIGN OF INTERACTIVE E-LEARNING BASED ON THE STEM APPROACH ASSISTED BY MOODLE H5P ON ROTATIONAL MOTION MATERIAL: Rancangan E-learning Interaktif Berbasis Pendekatan STEM Berbantuan Moodle H5P pada Materi Gerak Rotasi - Sayyatul Rohma Ahfa; I Made Astra; Hadi Nasbey (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
The industrial revolution 4.0, characterised by the integration of advanced technologies such as artificial intelligence, Internet of Things, and cloud computing, has changed the educational landscape. One of its most significant impacts is the use of technology in the learning process, which presents new opportunities and challenges for education. Based on the results of a needs analysis of 63 public high school students in Tangerang Regency grade 11 in 2024. There is a problem that students have difficulty in understanding rotational motion material, this is based on the results of the needs analysis that has been tested. The purpose of this study is to determine whether interactive e-learning based on STEM approach assisted by moodle H5P is feasible to be used as physics learning media on high school rotational motion material. This research uses the Research and Development (R&D) method with the ADDIE development model and involves high school students in grade 11 specialisation in physics with a total of 63 students. The final product in this research is an interactive e-learning design that can be accessed using the moodle site that has been developed, so that it can facilitate access to its use for students through their electronic devices.